Analisis Faktor-Faktor yang Mempengaruhi Keselamatan Pelayaran di PT. Pelni Cabang Waingapu - Putri, Candra Oktyasari; Parengu, Misericordia (Politeknik Bumi Akpelni, 2023)
Shipping safety is a condition of meeting ship safety and security requirements concerning the transportation of waters, ports, and the maritime environment. East Nusa Tenggara Province is an Archipelago Province, so sea transportation is very strategic in the context of accessibility from/to regions/regions in East Nusa Tenggara. This study aims to determine the influence of Crew Resources, Ship Safety Equipment, and Weather on Shipping Safety at PT. Pelni Waingapu Branch. The population in this study is passengers aboard KM Awu, which PT owns. Pelni Waingapu Branch and the sample used in this study were 100 respondents. The sampling technique used is the non-probability sampling purposive sampling type. The data is analysed using multiple linear regression with the help of (software) Statistical Package For Social Science (SPSS) Version 25. The regression formulation in this study is as follows: Y = 0,733 + 0,333X1 + 0,203X2 + 0,385X3 + µ. This equation shows that the most dominant variable affecting shipping safety is the weather variable, with a regression coefficient of 0.385. The R2 (R Square) test obtained results of 0.561 or 56.1%, which means that Shipping Safety is influenced by the variables of Crew Resources, Ship Safety Equipment, and Weather, which is 56.1%, and other factors that affect Shipping Safety at PT. Pelni Waingapu Branch is 43.9%.